Neoadjuvant chemotherapy prior to radical cystectomy for non-muscle invasive bladder cancer: national trends and pathologic outcomes - Davis, Kailey; Orf, Jeffrey; Ballon-Landa, Eric; Hamilton, Zachary (Frontiers in Oncology, 2024)
Background: There is a sparsity of literature on treatment outcomes for patients with non-muscle invasive bladder cancer (NMIBC) who received neoadjuvant chemotherapy (NAC). We aim to analyze the outcomes associated with the use of NAC prior to radical cystectomy for NMIBC utilizing the National Cancer Database.Materials/Methods: The National Cancer Database bladder dataset was evaluated for patients with NMIBC and known pT staging undergoing RC from 2006-2016. The primary outcome was the utilization of NAC. The secondary outcomes were pathologic down staging to pT0, positive surgical margins, 30-day readmission, and overall survival.The proportion of patients receiving NAC prior to radical cystectomy for NMIBC increased from 8.6% in 2006 to 14.8% in 2016. Those who received NAC had significantly higher tumor stages (cT1 vs cTa/is) with 85.7% of patients receiving NAC presenting with cT1 as opposed to only 82% in those not receiving NAC (p < 0.001).Similarly, there were significantly more patients who were cN+ in the NAC group as compared to those who did not receive NAC (5.5% vs. 1.1%, p < 0.001). For patients who received NAC, the rate of downstaging to pT0 was 12.7% as compared to only 3.3% in patients who did not receive NAC (p < 0.001). There was no significant difference comparing the rates of positive margins or 30-day readmissions between groups. On multivariable logistic regression for pathologic downstaging, NAC was significant (OR 4.1, p < 0.05). There was no significant difference in overall survival between patients treated with or without NAC.